PENGEMBANGAN MODEL PERMAINAN OUTBOUND CARTERPILLAR RACE PADA SISWA KELAS V SD N PURWOYOSO 01 KECAMATAN NGALIYAN KOTA SEMARANG TAHUN AJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine the results of Model Development Outbound game "carterpillar race" in the fifth grade elementary school KecamatanNgaliyan Purwoyoso 01 Semarang Academic Year 2012/2013. This study is a research method that refers to the development of models of Borg & Gall development that has been modified. Analysis of data using questionnaires for students, specialists and experts penjas learning. Of small-scale test results obtained from the data as follows: a small-scale trial of cognitive aspects of 83% (good), 91% affective aspect (very good), psychomotor aspects 81% (good) and cognitive aspects of field trials 85% (very good ), the affective aspect 93% (very good), psychomotor aspects of 84% (good). Based on the research data, it was concluded that the Development Model permaian Outbound "carterpillar race" in Class V Elementary School Purwoyoso 01 Kecamtan Ngaliyan Semarang Academic Year 2012/2013, so that the model can be applied to this game as a learning model.